2014
DOI: 10.1002/pri.1606
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Low‐Level Laser Therapy for Shoulder Tendinopathy: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: This review shows that optimal LLLT can offer clinically relevant pain relief and initiate a more rapid course of improvement, both alone and in combination with physiotherapy interventions. Our findings challenge the conclusions in previous multimodal shoulder reviews of physiotherapy and their lack of intervention quality assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 53 publications
(116 reference statements)
0
62
0
Order By: Relevance
“…A promising treatment in wound healing is the low-level light therapy (LLLT), a system using low-power light to stimulate cellular function and biological activity. 7 Recent studies showed the importance of LLLT in pain, 8,9 skin, 7,10 and wound 11,12 care. In recent years, investigators have examined the effect of LLLT on the DFU treatment, 13 finding improvement in pain scores [14][15][16] or in clinical foot sensation.…”
Section: Introductionmentioning
confidence: 99%
“…A promising treatment in wound healing is the low-level light therapy (LLLT), a system using low-power light to stimulate cellular function and biological activity. 7 Recent studies showed the importance of LLLT in pain, 8,9 skin, 7,10 and wound 11,12 care. In recent years, investigators have examined the effect of LLLT on the DFU treatment, 13 finding improvement in pain scores [14][15][16] or in clinical foot sensation.…”
Section: Introductionmentioning
confidence: 99%
“…This was the first systematic review of the effects of LLLT on pain and functional outcomes in patients with shoulder tendinopathy. Previous reviews have assessed the effects of LLLT therapy on different tendinopathies, or have included studies that addressed the use of both low and high power laser therapy 26 . This review was conducted in accordance with PRISMA 14 recommendations, ensuring consistency and uniformity in systematic review reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Their effect is based on mechano-thermal phenomena which in some way affect the nociceptive afferent nerve fibers [19,20], changing their activity and suppressing neurostimulators resulting from the pain receptors of peripheral nerves [21]. The analgesic effect of LLLT however, has been supported by systematic reviews of both medical [22,23] and dental fields [24].…”
Section: Action Mechanism Of Llltmentioning
confidence: 99%